Market Trends and Demand Analysis for Seaweed Products in Occidental Mindoro Implications for Business Development - Maria Angelica Sunga; Fye Dunaway R. Asio; Jason G. Ramirez (Bina Nusantara University, 2025)
Seaweeds are the top aquaculture species produce in the Philippines, where Region IV-B including Occidental Mindoro has been the 2nd top producers in 2018. Therefore, the main focus of this study is to generate new ideas about the market trends and demand for seaweeds which in turn will be beneficial in the creation of new products and innovation. This research was conducted in Occidental Mindoro including 100 farmers and 384 consumers of seaweeds and carefully selected using random sampling. A two-fold survey instrument and a descriptive method were used in collecting and analyzing the data. There is a downturn with the production volume of some farmers of about 10-20% in recent years because of the changes or fluctuations in market demand and usually producing 1-5 tons. While, majority of the farmers are cultivating less 100 kgs. for each species namely: Eucheuma denticulatum (spinosum), Kappaphycus striatum (vanguard), Kappaphycus alvarezii (cottonii) using just one farm site. The farmers refused the adoption of technology due to limited financing; and development of seaweed-based products are occasionally done. Fluctuations in the selling price is experience in a very frequent manner and has vastly been acknowledged seasonal production variations as an influencing factor. The major strategy used in seaweeds is competitive pricing, allowing this sector to take advantage within the competition and only few are engaged in product innovation. The demand analysis implies that there is a promising and interesting market for product development and innovation focusing on the seaweed products that are fresher, nutritious, and compliant to food safety regulations. Based on the findings, it is suggested that the seaweed farmers shall adopt technology and be engaged in training programs that supports environmental sustainability; and be involved in product development and innovation addressing the health benefits and compliance with food safety regulations.